Educational Social Skills of Mothers: Relations between Genders and Types of Institutions - Maia, Fátima de Almeida; Soares, Adriana Benevides (Perspectivas em Análise do Comportamento, 2018)
The present study aims at identifying to what extent social abilities are involved in mother’s parental educational practices with their children and compare mothers’social educational abilities in relation to boys and girls, in public as well as private schools. Participants were 6th grade students between 11 and 12 years old - 3 public school mothers (2 mothers of girls and 1 mother of a boy) and 3 private school mothers (2 mothers of boys and 1 mother of a girl). The instrument was a semi-structured interview based on Parental Educational Social Skills Interview Script (RE-HSE-P). The results of the interaction showed that mothers of public school boys and girls presented a good repertoire of HSE-P, but in negative practices, they showed a clinical repertoire influencing behavioural problems Sons and daughters show a good repertoire of social skills, but they revealed behavioral problems. Thus, it is considered fundamental, a broad discussion about the behavior of mothers in the use of a repertoire of social skills while interacting with their children, observing how they act and influence their children’s behavior.